2001
DOI: 10.1152/ajpheart.2001.280.3.h1376
|View full text |Cite
|
Sign up to set email alerts
|

In vivo regulation of Na/Ca exchanger expression by adrenergic effectors

Abstract: The Na/Ca exchanger encoded by the NCX1 gene plays an important role in calcium homeostasis in cardiac muscle. We previously identified three in vitro signaling pathways that are of major importance in the regulation of Na/Ca exchanger gene expression in neonatal cardiac myocytes, the protein kinase A (PKA) and protein kinase C (PKC) pathways, and intracellular Ca(2+). To determine whether these pathways are important in vivo, we stimulated the PKA and PKC pathways and examined functional expression of the Na/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 27 publications
1
28
0
Order By: Relevance
“…SERCA, NCX, and L-type Ca 2ϩ channel current density levels were normalized by propranolol treatment, explaining the improved Ca 2ϩ handling in treated TOT mice. The shared normalization of SERCA, NCX, and L-type Ca 2ϩ channel by ␤-blockade in our heart failure model suggests that common regulatory pathways or Ca 2ϩ -handling proteins may exist downstream of ␤-receptors (14,16). SERCA and L-type Ca 2ϩ channel demonstrated enhanced restoration in protein content compared with NCX, suggesting that SERCA and L-type Ca 2ϩ channel regulation may be linked to ␤-adrenergic blockade given the short duration of treatment (16).…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…SERCA, NCX, and L-type Ca 2ϩ channel current density levels were normalized by propranolol treatment, explaining the improved Ca 2ϩ handling in treated TOT mice. The shared normalization of SERCA, NCX, and L-type Ca 2ϩ channel by ␤-blockade in our heart failure model suggests that common regulatory pathways or Ca 2ϩ -handling proteins may exist downstream of ␤-receptors (14,16). SERCA and L-type Ca 2ϩ channel demonstrated enhanced restoration in protein content compared with NCX, suggesting that SERCA and L-type Ca 2ϩ channel regulation may be linked to ␤-adrenergic blockade given the short duration of treatment (16).…”
Section: Discussionmentioning
confidence: 76%
“…The shared normalization of SERCA, NCX, and L-type Ca 2ϩ channel by ␤-blockade in our heart failure model suggests that common regulatory pathways or Ca 2ϩ -handling proteins may exist downstream of ␤-receptors (14,16). SERCA and L-type Ca 2ϩ channel demonstrated enhanced restoration in protein content compared with NCX, suggesting that SERCA and L-type Ca 2ϩ channel regulation may be linked to ␤-adrenergic blockade given the short duration of treatment (16). These findings are in agreement with other studies that report improved SERCA and NCX levels after ␤-blockade in different heart failure models (19,28,47).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The mechanism regulating Ca 2 transporter gene expression is also unclear. Recently, Golden et al showed that α and β adrenergic agonists increased the expression of NCX1 mRNA in the adult rat heart (30). Changes in hormonal factors might affect gene expression in the progression from cardiac hypertrophy to failure.…”
Section: Na /Ca 2 Exchanger In Hypertrophy and Failurementioning
confidence: 99%
“…Norepinephrine, the primary neurotransmitter of the sympathetic nervous system, mediates cardiac ionotropic, chronotropic, and lusitropic effects via multiple ionic mechanisms, including Ca 2ϩ homeostasis (49). Furthermore, adrenergic receptor activation alters the expression of genes that encode cardiac Ca 2ϩ regulatory proteins (13,29). The ability of cardiac myocytes to maintain cytosolic Ca 2ϩ concentration within a tightly controlled range is crucial for cardiac electrical stability (12).…”
mentioning
confidence: 99%